n-6=(-13)

Simple and best practice solution for n-6=(-13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n-6=(-13) equation:


Simplifying
n + -6 = (-13)

Reorder the terms:
-6 + n = (-13)
-6 + n = -13

Solving
-6 + n = -13

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + n = -13 + 6

Combine like terms: -6 + 6 = 0
0 + n = -13 + 6
n = -13 + 6

Combine like terms: -13 + 6 = -7
n = -7

Simplifying
n = -7

See similar equations:

| -4-(7-11)=x | | 5(x+2)-4=21 | | 1-4x+17+2x=19-6x | | 5x+4=2x^2 | | j^2=-9j+9 | | X^3-5400=432 | | 7x+13x-5-15=-10-10+14x+6 | | 17+2x+19-6x=1-4x | | 180=(2x+8)+(7x-2) | | -120=-6(3x+2) | | 3x^2+15=207 | | -3(4)-(12)=-24 | | (4u^2-2u-3)+(3u^2-u+4)= | | 180=(2x+8)(7x-2) | | a^2+13a+8=0 | | 57+k=123.14 | | 2x^5+20x^4+48x^3=0 | | 7v=8v^2 | | 320=x(2x+6) | | -1(1/4-4)=3u-17/4 | | 3G-2g=11 | | 3x+18y=120 | | 425=25x-[10x+250] | | 5p-7=-3 | | log(9+6x)=1+log(x-9) | | (2x+8)(6x+12)=180 | | Q-265=-346 | | (4y^2+2y-8)-(7y^2+4-y)= | | (2y-5)/7=9 | | 4x^2+5x+16=0 | | 4v^2-9v+9=2 | | 12+8-20= |

Equations solver categories